Using Teleost Fish to Discern Developmental Signatures of Evolutionary Adaptation From Phenotypic Plasticity in Brain Structure - Hall, Zachary J.; Tropepe, Vincent (Frontiers in Neuroanatomy, 2020)
Traditionally, the impact of evolution on the central nervous system has been studied by comparing the sizes of brain regions between species. However, more recent work has demonstrated that environmental factors, such as sensory experience, modulate brain region sizes intraspecifically, clouding the distinction between evolutionary and environmental sources of neuroanatomical variation in a sampled brain. Here, we review how teleost fish have played a central role in shaping this traditional understanding of brain structure evolution between species as well as the capacity for the environment to shape brain structure similarly within a species. By demonstrating that variation measured by brain region size varies similarly both inter- and intraspecifically, work on teleosts highlights the depth of the problem of studying brain evolution using neuroanatomy alone: even neurogenesis, the primary mechanism through which brain regions are thought to change size between species, also mediates experience-dependent changes within species. Here, we argue that teleost models also offer a solution to this overreliance on neuroanatomy in the study of brain evolution. With the advent of work on teleosts demonstrating interspecific evolutionary signatures in embryonic gene expression and the growing understanding of developmental neurogenesis as a multi-stepped process that may be differentially regulated between species, we argue that the tools are now in place to reframe how we compare brains between species. Future research can now transcend neuroanatomy to leverage the experimental utility of teleost fishes in order to gain deeper neurobiological insight to help us discern developmental signatures of evolutionary adaptation from phenotypic plasticity.